USP14-mediated metabolic competition impairs CD8+ T cell immunosurveillance in hepatocellular carcinoma - Yichuan Yuan; Yi Niu; Zhenkun Huang; Yunxing Shi; Zhu Lin; Dinglan Zuo; Chengrui Zhong; Kai Li; Xin-Yuan Guan; Yunfei Yuan; Binkui Li (Proceedings of the National Academy of Sciences, 2025)
Hepatocellular carcinoma (HCC) frequently develops resistance to CD8+ T cell–based immunotherapy, yet the mechanisms driving this immune evasion remain poorly understood. To identify tumor-intrinsic regulators of immunotherapy resistance and explore therapeutic strategies to restore T cell–mediated tumor control, we employed three functional genomics approaches using in vitro and in vivo CRISPR screening. Cancer USP14 was identified as the critical immune evasion driver. USP14-high HCC patients exhibited poorer anti-PD1 antibody therapy responses and reduced CD8+ T cell infiltration. Inhibition of USP14 suppressed HCC cell growth in coculture with activated CD8+ T cells and restored cocultured CD8+ T cell cytotoxicity. In vivo USP14 targeting synergized with anti-PD1 antibody therapy. Mechanistically, USP14 deubiquitinated and stabilized GLUT1 through the removal of Lys-48-linked ubiquitin chains at Lys-245, which enabled HCC cells to outcompete CD8+ T cells for glucose, generating a glucose-deprived tumor microenvironment that suppressed CD8+ T cell function. Our findings show USP14 in cancer has a proimmunoevasive role in CD8+ T cell–based tumor immunity through GLUT1-mediated glucose competition. These findings position USP14 inhibitors as promising adjuvants to enhance immunotherapy efficacy in HCC, providing actionable insights for overcoming resistance.